Pembelajaran berbicara melalui podcast dengan metode ESA (Engage, Study, Activate) untuk siswa SMA di kota Bekasi - Widiyarto, Sigit; Saidiman, Saidiman (Universitas Mulawarman, 2026)
The suboptimal speaking proficiency among eleventh-grade students in Bekasi has prompted the development of novel instructional methods. Currently, only 36% of students can speak accurately and in accordance with linguistic rules. To address this, the present study explores the implementation of podcast-integrated lessons using the ESA (Engage, Study, Activate) framework and evaluates its effectiveness in enhancing student performance. Adopting an experimental approach with a one-group pretest-posttest design, the study involved 36 participants. Data were gathered through assessments conducted before and after the intervention, utilizing narrative material from the podcast “Jalan-jalan dan makan-makan di Palembang.” Analysis revealed a significant improvement, with mean scores rising from 48.39 in the pretest to 71.69 in the posttest (p = 0.000 via paired sample t-test). Furthermore, the N-Gain calculation yielded an average of 0.42, placing the improvement in the moderate category. These findings suggest that integrating podcasts with the ESA method not only effectively boosts speaking skills but also fosters greater student engagement and motivation, offering a valuable strategy for innovative language pedagogy at the high school level.